Rethinking authority in the Carolingian empire : ideals and expectations during the reign of Louis the Pious (813-828) - Kramer, Rutger (Early medieval North Atlantic., 2019)
By the early ninth century, the responsibility for a series of social, religious and political reforms had become an integral part of running the Carolingian empire. This became especially clear when, in 813/4, Louis the Pious and his court seized the momentum generated by their predecessors and broadened the scope of this correctio ever further. These reformers knew they constituted a movement greater than the sum of its parts; the interdependence of imperial authority and ecclesiastical reformers was driven by comprehensive, yet surprisingly diverse expectations.00Taking this diversity as a starting point, this book takes a fresh look at these optimistic decades. Extrapolating from a series of detailed case studies rather than presenting a grand narrative, it offers new interpretations of contemporary theories of correctio, and shows the self-awareness of its main instigators as they pondered what it meant to be a good Christian in a good Christian empire.